GLOBALIZATION OF INTERNATIONAL FINANCIAL MARKETS - Tubolec, I. I.; Tkalich, O. V. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The article deals with one of the components of globalization - the globalization of financial markets. The article considers financial markets, which are the component of globalization. The study investigates the international financial institutions that together form the international financial infrastructure and the main subjects of financial globalization. The study investigates the international financial institutions, which collectively form the international financial infrastructure and main subjects of financial globalization. The segments of the global financial market, which include the global debt market, the global stock market, other global financial markets (precious metals, real estate insurance), the global currency market, are considered. The article considers the segments of the global financial market, such as the global debt market, the global stock market, the global currency market and other global financial markets (precious metals, real estate insurance etc.). The article presents the prospects of global financial markets, such as high world standards, higher level of diversification, higher liquidity and professional risk management. It is established that the basis of the globalization of the financial system lies in the interaction of such phenomena as: technological progress; growing competition: on the one hand, between lending and financial institutions in the financial markets, and on the other hand, between the financial markets themselves, due to the significant development of information technology and telecommunications; restructuring of credit and financial; wide internationalization of business due to the increasing transnational nature of corporations; consolidation of regional integration associations (in Europe - Economic and Monetary Union); weakening of the firm control over the implementation of international agreements related to the movement of capital stock exchanges; - macroeconomic stabilization and reform in a number of developing and transition countries that have created a favorable climate for foreign investors; widespread use of the "principle of the lever". We investigated that the integration of international capital markets, merger of financial institutions, the tendency to increase speculative operations in the financial markets and financial crises are the global trends in the development of international financial markets in the requisition of globalization. It is proved that the, the emergence of the global financial space is represented by an increase in international financial flows, volumes of all types of international transactions, an increase in the number of companies and financial groups that operate outside of the national financial systems.